Thickness optimization of GaN layers by in‐situ observation of GaN MOVPE on Si (111). Issue 11 (25th September 2013) - Liu, Cai; Sodabanlu, Hassanet; Sugiyama, Masakazu; Nakano, Yoshiaki; Yamaguchi, Hiroshi; Kumakura, Kazuhide
Abstract For MOVPE grown GaN on Si (111) employing low temperature AlN interlayers, in terms of compressive stress introduction to avoid cracking, factors determining the proper thickness of GaN layers were investigated, with the help of in‐situ observation of multi‐wavelength reflectance patterns and curvature transition. For the 1st GaN layer, the stress behavior of it depends on the growth conditions of AlN buffer layer. For the case on an improper AlN buffer layer, GaN takes tensile stress easily and thus its thickness should be limited to reduce the amount of tensile stress. On the contrary, on the optimized AlN buffer layer, the GaN on it was compressively strained and its thickness can be large to introduce more compressive stress. For GaN layers in between AlN interlayers, the thickness should be limited to be less than the critical thickness in which the layer starts to relax. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)